Functional and Cosmetic Outcome of Bipolar Release in Congenital Muscular Torticollis among Children: An Observational Study from the Tertiary Care Center of KPK - Waseem Khan, Asghar Ali Khan, Noor-U-Rahman, Muhammad Salar Khan, Muhammad Jawad Saleem, Muhammad Ilyas (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Congenital muscular torticollis (CMT) is a common musculoskeletal condition in children which may cause functional and cosmetic problems if not treated at an early stage. This study was undertaken to assess the functional and cosmetic results of bipolar release of the sternocleidomastoid muscle in children presenting with CMT at tertiary care center of KPK. Methodology: This prospective observational study was done at Hayatabad Medical Complex Peshawar from Jan 2022 to July 2023 on 30 children of age between 4-16 years who presented with CMT. All patients underwent bipolar release after conservative management failure. Functional outcomes were evaluated with cervical rotation and lateral flexion and cosmetic outcomes were head tilt correction, facial asymmetry, and scar formation. Preoperative and postoperative values were compared with paired t-test and stratification analysis was done according to age, gender, and side of involvement. Results: Study was male dominant with 53.3% of male children and the mean age of overall population was 10.23 ± 3.53 years. We noted an excellent and good response in 46.7% and 33.3% of patients respectively. Only 6.7% patient showed poor outcome. A significant improvement was seen in cervical rotation 44.88°±6.37 to 75.14°±8.13, and lateral flexion from 24.49°±4.26 to 50.66°±7.02 (p-value <0.001). Complete correction of head tilt was observed in 63.3%, and facial asymmetry improved in 70% of cases. Upon stratification analysis, no significant association (p-value >0.05) was found among confounders for any outcome. Conclusion: Bipolar release is safe and effective treatment for congenital muscular torticollis in children that offers great functional improvement and good cosmetically acceptable results regardless of patient demographics. Keywords: Congenital muscular torticollis, children, sternocleidomastoid muscle, facial asymmetry, head tilt, flexion, rotation